Nanoscale phase separation in quasi-uniaxial and biaxial strained multiferroic thin films - Qi, Yajun (2014)
Nanoscale phase separation was investigated in epitaxial strained BiFeO3thin films on LaAlO3 single crystal substrate. In biaxial strained thin films, nanoscale mixtures of the tetragonal-like and rhombohedral-like phases occur with a film thickness above 35 nm. For 10-30 nm ultrathin ones, tetragonal-like single phase is confirmed using synchrotron x-ray and the atomic force microscopy studies. However, nanoscale phase separations are still observed in quasi-uniaxial transmission electron microscopy foil specimens for those ultrathin films, indicating the phase separation emerges in a much smaller thickness in uniaxial constraint films than that in biaxial ones.